Modelling and experiments of glassy polymers using biaxial loading and digital image correlation. (15th December 2016) - Engqvist, Jonas; Wallin, Mathias; Ristinmaa, Matti; Hall, Stephen A.
Abstract: Experimental data are needed to evaluate constitutive models. The richer the experimental data, in terms of different deformation modes for example, the better the constraints on the model. To this end, the mechanical response of glassy polycarbonate (PC) is studied using biaxial tension experiments with novel sample geometries. Deformation fields are measured using full-field digital image correlation (DIC) to reveal a large difference in the strain localisation behaviour of the material depending on the amount of lateral deformation. The difference in the localisation behaviour is also reflected in the macroscopic force-displacement response. The experimental data acquired in the experiments are used to examine the ability of a physically-motivated constitutive model to predict the mechanical response of the material during biaxial deformation. To improve the numerical predictions, the elastic part of the constitutive model is modified such that the initial non-linear response due to volumetric deformation is accurately captured. This new elastic model is motivated by the experimental results, which show that the commonly used quadratic form of the elastic free energy results in a too stiff response during biaxial tension.